A Review of antecedents and effects of brand loyalty towards home appliances brands in Algeria - BOUREGA fatma; ABDELLI Mebarka (Journal of North African Economies, 2025)
This study at hand aims at highlighting the most significant brands loyalty antecedents through the purchase of specific home appliances in Algeria by taking a 250 respondent’s survey to analyses and interpretation. The PLS method’s results manifested a clear and direct effect between satisfaction and trust, trust and attachment, attachment and commitment with the latter being linked to the costumer’s loyalty to the commercial brand. It has also determined a positive yet indirect impact amid satisfaction, attachment, commitment and loyalty on one hand, and trust with commitment plus attachment with loyalty on the other hand.